Pemberdayaan Masyarakat Melalui Penerapan Teknik Integrasi Tanaman-Ternak Berbazis Zero Waste Agriculture - Nur Hayati; Sitti Rahmawati; Usman Made; Haerani Maksum; Sri Anjar Lasmini; Rosmini Rosmini (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2021)
The potential of agricultural and livestock resources in Pombewe Village is quite available but not yet optimally utilized by the community. Agricultural land is still largely abandoned and livestock are still left to graze themselves. The problem faced by the community is the lack of skills on how to improve agricultural products. This community empowerment program aims to assist the community in applying the integration of zero waste agriculture techniques. The method applied is community development with activities in the form of counseling, training, demonstration plots and mentoring with output targets is to increase the community's insight, knowledge and skills. The results achieved were an increase in community knowledge and skills characterized by the ability of the community to use agricultural and livestock waste to be economically valuable by making liquid organic fertilizer, compost, and can cultivate forage grass as animal feed